Landslides and predisposing factors of the Southern Apennines, Italy - Mario, Bentivenga; Giacomo, Prosser; Paola, Guglielmi; Giuseppe, Palladino; Marco, Piccarreta; Katia, Straziuso; Francesco, Cavalcante (Journal of maps, 2023)
The Fiumarella di Corleto drainage basin is an emblematic sector of the southern Apennine thrust belt in the Basilicata region (Southern Italy), which is strongly affected by landslides. Landslides both affect the urban area and the facilities related to hydrocarbon exploitation, such as the pipelines and oil wells connected with the oil centre located just outside the eastern border of the study area. Based on a detailed field survey, supported by stereoscopic analysis, a landslide inventory map has been realized, which also reports the associated processes and landforms. The relationships between the different types of landslides and the various predisposing factors like outcropping lithologies, slopes steepness, slope exposition and land use have been also investigated. The acquired data relate to a geologically complex area of the southern Apennines subject to recent uplift and represent a fundamental contribution useful for the correct management of the territory.